2016
DOI: 10.1017/s1047951116000640
|View full text |Cite
|
Sign up to set email alerts
|

Lower spatial QRS-T angle rules out sustained ventricular arrhythmias in children with hypertrophic cardiomyopathy

Abstract: In children with hypertrophic cardiomyopathy, the spatial peaks QRS-T angle is associated with ventricular arrhythmia burden with high negative predictive value and odds ratio.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…The maximum vector-based QRS-T angle calculation is based on the notion that QRS and T wave orientations are defined by the maxima of the vector magnitudes within the corresponding orthogonal loops ( Cortez et al, 2017a ). That is, within the orthogonal system of ECG leads, time points and are selected such that and similarly , where , , and again specify QRS onset, QRS offset, and T wave offset, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The maximum vector-based QRS-T angle calculation is based on the notion that QRS and T wave orientations are defined by the maxima of the vector magnitudes within the corresponding orthogonal loops ( Cortez et al, 2017a ). That is, within the orthogonal system of ECG leads, time points and are selected such that and similarly , where , , and again specify QRS onset, QRS offset, and T wave offset, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…In 2000, however, the seminal report by Zabel et al, (2000) showed that the angle of the ventricular gradient, that is the 3-dimensional angle between the QRS and T wave orientations, is a potent predictor of mortality risk in survivors of acute myocardial infarction. Subsequently, the risk stratification strength of the QRS-T angle has been confirmed in a large number of studies including investigations of other ischaemic heart disease populations ( de Torbal et al, 2004 ; Malik et al, 2004 ), acute coronary syndrome ( Lown et al, 2012 ), heart failure ( Gotsman et al, 2013 ; Selvaraj et al, 2014 ; Sweda et al, 2020 ), hypertrophic ( Cortez et al, 2017a ; Cortez et al, 2017b ; Jensen et al, 2021 ) and dilated cardiomyopathy ( Li et al, 2016 ), diabetic patients ( Voulgari et al, 2010 ; Cardoso et al, 2013 ; May et al, 2017 ; May et al, 2018 ), renal patients on haemodialysis ( de Bie et al, 2013 ; Poulikakos et al, 2018 ); and many other populations and conditions ranging from systemic sclerosis ( Gialafos et al, 2012 ) and Chagas disease ( Zampa et al, 2014 ) to overall hospital ( Yamazaki et al, 2005 ) and general populations ( Kardys et al, 2003 ; Kors et al, 2003 ; Walsh et al, 2013 ). It has also recently been shown that QRS-T angle might be meaningfully combined with other ECG-based risk factors ( Hnatkova et al, 2022 ).…”
Section: Introductionmentioning
confidence: 91%
“…9 Electrocardiogram (ECG)-derived vectorcardiographic (VCG) repolarization parameters offer the possibility of objective T-wave morphology measure and have demonstrated significant diagnostic and prognostic value in patients at risk for sudden cardiac death. [10][11][12][13][14][15][16][17][18][19] ECG-derived VCG has shown prognostic utility in LQTS patients with prolonged QTc values, while in LQTS patients without QTc prolongation, neither spatial durations nor the spatial QRS-T angle was able to differentiate symptomatic from asymptomatic LQTS patients. 20,21 Assessment of the shape of the T-wave can be a way to identify patients with LQT2 without QTc prolongation at risk for cardiac events 4,9 ; however, qualitative methods may be operator-dependent and subject to interindividual variability.…”
Section: Introductionmentioning
confidence: 99%
“…Electrocardiogram (ECG)‐derived vectorcardiographic (VCG) repolarization parameters offer the possibility of objective T‐wave morphology measure and have demonstrated significant diagnostic and prognostic value in patients at risk for sudden cardiac death . ECG‐derived VCG has shown prognostic utility in LQTS patients with prolonged QTc values, while in LQTS patients without QTc prolongation, neither spatial durations nor the spatial QRS‐T angle was able to differentiate symptomatic from asymptomatic LQTS patients …”
Section: Introductionmentioning
confidence: 99%
“…In all hypertrophic, dilated and left ventricular non-compaction cardiomyopathies, ventricular arrhythmia may occur and heart failure may progress, resulting in death. The literature on the usefulness of the QRS-T angle in children with hypertrophic and non-compaction cardiomyopathies is limited [ 14 , 15 ]. To our knowledge, the QRS-T angle in children with idiopathic dilated cardiomyopathy (DCM) has not been assessed previously.…”
Section: Introductionmentioning
confidence: 99%